Epidemic spreading as a driving force of system evolution - Kwok, Elton Jia Wei. (2013)
Network models are graphical tools to aid illustration of relationships between things and processes, usually of a unifying theme. With network models, interconnected nodes can clearly describe the relationships of virtually all processes, regardless of scale, from a micro level (cellular) to a macro framework (food web). Recent studies have elevated the potency of these network models for they are found to be able to succinctly and accurately describe our interconnected world. Despite the importance of networks, little is understood about their structural framework and properties. The project aims to be at least successful in producing a simulation which can show the dynamics of system evolution in face of an epidemic. It will allow the author to have a more profound understanding of the dynamics of such phenomenon from the results obtained. This will enable us to investigate the role of epidemic in the evolution of system network.